Correlation between Blood Sodium and CD4 Level in Pediatrics with Human Immunodeficiency Virus Infection - Maulana, Shahdan Taufik; Umma, Husnia Auliyatul; Nugroho , Hari Wahyu (Journal of Maternal and Child Health, 2025)
Background: Electrolyte disorders such as hyponatremia are often found in human immunodeficiency virus (HIV) patients. It is closely correlated with HIV morbidity and mortality. Sodium levels have also been reported to correlate with cluster of differentiation 4 (CD4) in adult subjects, but it is not yet known how in children with HIV infection.This study conducted to analyze the correlation between electrolyte levels, especially sodium, and CD4 levels in children with HIV infection. Subjects and Method: Descriptive analytical study with a cross-sectional design. The subjects were 42 pediatric HIV patients aged 0-18 years who were willing to undergo sodium and CD4 level examinations. Subjects with liver cancer, liver cirrhosis and cardiovascular disease and opportunistic infections in HIV were excluded. Subjects were selected by consecutive sampling. The dependent variables was blood sodium levels, while the independent variables was CD4 counts, and the confounding variables were age, and ARV duration use. Sodium levels were measured using the Cbs400, Jokoh ex-d and smarlyte devices while CD4 levels were measured using the BD FACSCount device by flow cytometry. The correlation between sodium and ARV duration use on CD4 levels analyzed by Pearson test, while correlation between patient’s age and CD4 levels analyzed by Spearman rank test. The multiple linear regression used to control the confounding variables. Results: The average sodium level in pediatric HIV patients at Dr. Moewardi Surakarta Regional General Hospital (Mean= 131.19; SD= 5.68 mEq/L), while the average CD4 level (Mean= 940.40; SD= 464.81 cells/μL). Pearson test showed a positive and weak correlation between sodium levels and CD4 counts (r= 0.32; p = 0.040), meaning that the higher the sodium level, the higher the CD4 count. There was a negative and very weak correlation with the duration of ARV use (r= -0.18; p= 0.254), meaning that the higher the sodium level, the lower the CD4 count. Spearman Rank test showed a correlation between age and CD4 count (r= -0.52; p<0.001), meaning that the older the person, the lower the CD4 count. The results of linear regression showed that there was a significant influence between sodium levels on CD4 count (b= 24.99; p= 0.029) and patient age (b= -55.21; p=0.003). Conclusion: Sodium levels have a moderate positive correlation with CD4 levels in pediatric patients with HIV infection. Examination of sodium levels can be an additional parameter in routine monitoring of the immunodeficiency status of pediatric HIV patients.